Impact of working conditions on the quality of working life: Case manufacturing sector colombian Caribbean Region (2015)
This paper investigate the impact of Working Conditions on Quality of Working Life of human talent of manufacturing sector in the Colombian Caribbean region. To analyze this process interviewed 518 employees in the sector. The experimental design used was not descriptive cross type; each participant was applied an interview with the instrument of Working Conditions and Quality of Working Life Tool (Wage and Subjective Conditions). Data were analyzed using correlation analysis and logistic regression models. The results showed that the thermal environment and safety standard at work positively affects the Quality of Working Life. These results show that the relationship between working conditions and CVL is based on competition and far from linear or simple relationship relating to the consideration of the presence or absence of working conditions. This has implications when formulating policies, programs and interventions to prevent the negative effects of working conditions and enhance the industrial safety within industrial companies.